Rational Design of pH‐Responsive DNA Motifs with General Sequence Compatibility. (1st October 2019) - Fu, Wenhao; Tang, Linlin; Wei, Gaohui; Fang, Liang; Zeng, Jie; Zhan, Renjie; Liu, Xuemei; Zuo, Hua; Huang, Cheng Zhi; Mao, Chengde
Abstract: Reconfigurable molecular events are key to molecular machines. In response to external cues, molecular machines rearrange/change their structures to perform certain functions. Such machines exist in nature, for example cell surface receptors, and have been artificially engineered. To be able to build sophisticated and efficient molecular machines for an increasing range of applications, constant efforts have been devoted to developing new mechanisms of controllable structural reconfiguration. Herein, we report a general design principle for pH‐responsive DNA motifs for general DNA sequences (not limited to triplex or i‐motif forming sequences). We have thoroughly characterized such DNA motifs by polyacrylamide gel electrophoresis (PAGE) and fluorescence spectroscopy and demonstrated their applications in dynamic DNA nanotechnology. We expect that it will greatly facilitate the development of DNA nanomachines, biosensing/bioimaging, drug delivery, etc. Abstract : DNA‐Bewegung : Die rationale Entwicklung von pH‐responsiven DNA‐Motiven wird beschrieben. Das Prinzip ist nicht auf spezielle DNA‐Motive beschränkt und kann allgemein angewendet werden. Die entwickelten DNA‐Motive werden durch Polyacrylamid‐Gelelektrophorese (PAGE) und Fluoreszenzspektroskopie analysiert und ihr Potenzial für Anwendungen in der dynamischen DNA‐Nanotechnologie wird demonstriert.